TEACHER WELL-BEING GURU GEN-Z: PERAN WORK LIFE BALANCE DAN PERCEIVED ORGANIZATIONAL SUPPORT - Sofiya Najwa Herdianti; Nita Rohayati; Regi Ramadan (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Teacher well-being has become an important issue due to increasing work demands, administrative pressures, and emotional challenges faced by teachers, particularly Generation Z teachers who are in the early stages of their careers. Although previous studies have examined various factors associated with teacher well-being, studies simultaneously examining the roles of Work-Life Balance and Perceived Organizational Support in Teacher Well-Being among Generation Z teachers remain limited, particularly in Karawang. This study aimed to examine the effects of Work-Life Balance and Perceived Organizational Support on Teacher Well-Being among Generation Z teachers in Karawang. This study employed a quantitative approach with a predictive correlational design. The participants were 204 Generation Z teachers aged 19–29 years residing in Karawang, selected using convenience sampling. Data were collected using the Teacher Well-Being Scale, Survey of Perceived Organizational Support, and Work-Life Balance Scale and analyzed using multiple linear regression. The results showed that Work-Life Balance and Perceived Organizational Support each had a positive and significant effect on Teacher Well-Being. Simultaneously, both variables also had a significant effect on Teacher Well-Being among Generation Z teachers in Karawang. These findings highlight that maintaining a balance between work and personal life and perceiving adequate organizational support are important factors in promoting the well-being of Generation Z teachers. The findings imply that schools should develop work policies that facilitate work-life balance, recognize teachers’ contributions, and strengthen organizational support for teachers’ needs and well-being. ABSTRAK Teacher Well-Being menjadi isu penting seiring meningkatnya tuntutan kerja, tekanan administratif, dan tantangan emosional yang dihadapi guru, terutama guru Generasi Z yang berada pada tahap awal karier. Meskipun berbagai penelitian telah membahas faktor-faktor yang berkaitan dengan kesejahteraan guru, kajian yang secara simultan menguji peran Work-Life Balance dan Perceived Organizational Support terhadap Teacher Well-Being pada guru Generasi Z masih terbatas, khususnya di Karawang. Penelitian ini bertujuan untuk mengetahui pengaruh Work-Life Balance dan Perceived Organizational Support terhadap teacher well-being pada guru Generasi Z di Karawang. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional prediktif. Partisipan berjumlah 204 guru Generasi Z berusia 19–29 tahun yang berdomisili di Karawang dan dipilih menggunakan teknik convenience sampling. Pengumpulan data dilakukan menggunakan teacher well-being Scale, Survey of Perceived Organizational Support, dan Work-Life Balance Scale. Data dianalisis menggunakan regresi linear berganda. Hasil penelitian menunjukkan bahwa Work-Life Balance dan Perceived Organizational Support masing-masing berpengaruh positif dan signifikan terhadap teacher well-being. Secara simultan, kedua variabel juga terbukti berpengaruh signifikan terhadap teacher well-being pada guru Generasi Z di Karawang. Temuan ini menegaskan bahwa kemampuan menjaga keseimbangan antara kehidupan kerja dan pribadi serta persepsi terhadap dukungan organisasi merupakan faktor penting dalam mendukung kesejahteraan guru Generasi Z. Implikasinya, sekolah perlu mengembangkan kebijakan kerja yang mendukung keseimbangan kehidupan kerja, memberikan apresiasi terhadap kontribusi guru, serta memperkuat dukungan terhadap kebutuhan dan kesejahteraan guru.